The placental transfer of erythromycin in human pregnancies with group B streptococcal infection - Bulska, Magdalena; Szcześniak, Piotr; Pięta-Dolińska, Agnieszka; Oszukowski, Przemysław; Orszulak-Michalak, Daria (Ginekologia polska, 2015)
The aim of this study was to investigate the effectiveness of erythromycin in preventing fetal and intrauterine group B streptococcal (GBS) infections. The study evaluated the penetration of erythromycin through the placenta, by comparing umbilical vein and maternal serum erythromycin concentrations. The study subjects were 42 pregnant women, with GBS-positive screening or whose laboratory screening was not available, who delivered between 17th April 2013 and 22nd July 2013. The women were given 600 mg of erythromycin intravenously. After delivery blood was drawn from the mother's antecubital vein and umbilical cord vein. Serum erythromycin concentrations were evaluated using enzyme-linked immunosorbent assay (ELISA) kit. The percentage and correlation between umbilical vein and maternal serum erythromycin concentration were calculated. Based on regression function parameters selected factors: maternal age, maternal body weight, gestational age at delivery related to the umbilical vein serum erythromycin concentration, were investigated. Results: A total of 42 umbilical vein-maternal serum pairs were included in the analysis. The mean umbilical vein-maternal serum erythromycin concentration percentage was 2.64 ± 1.55%. There was a moderate correlation between umbilical vein serum and maternal serum erythromycin concentration. Pregnancy complications and selected variables of mothers in control group had no effect on the serum erythromycin concentration in the umbilical vein. Intravenous application of erythromycin at a dose of 600 mg, allowed to achieve therapeutic concentration in maternal serum. However, when it comes to placental transfer of erythromycin, the lack of therapeutic concentration in umbilical vein serum was observed. The limited transplacental transfer of erythromycin, which was approximately 2.6%, suggests compromised efficacy in the treatment of intrauterine fetal infections. On the other hand, the placenta seems to produce an effective barrier reducing the fetal exposure when erythromycin is used exclusively to treat maternal infections.